دور مخرجات نظام المعلومات المحاسبي في عملية التقويم المصرفي وفق متطلبات camels ( دراسة تحليلية في المصرف العقاري السوري ) - حبيب سمر (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تميزت بيئة عمل المصارف خلال السنوات الأخيرة بالاتجاه نحو توسيع تشكيلية الخدمات والعمليات المصرفية بما يتوافق مع تطورات العصر و تقانة المعلومات وعالم الاتصالات، وحمل هذا الجانب العديد من الايجابيات التي من شأنها زيادة ثقة ورضا العملاء بالمصرف، مما يحقق له قدرة أكبر في الحفاظ على عملائه واستقطاب عملاء جدد، الأمر الذي ينعكس على أدائه بشكل جيد، إلا أن ذلك من جهة أخرى زاد معه تعرض عمل المصارف إلى العديد من المخاطر على اختلافها، فمنها ما هو مرتبط بعوامل داخلية خاصة بالمصرف وإدارته، ومنها ما هو خارجي ومصدره تغييرات البيئة المحيطة بعمل المصرف، مما فرض بالضرورة على المصرف أولويات تضمن بقاءه في سوق العمل المصرفي في ظل المنافسة المتسارعة وأهم هذه الأولويات تدعيم رأس المال والاحتياطيات بما ينسجم مع مستوى المخاطر التي فرضتها هذه البيئة الجديدة والمنفتحة، وركزت هذه الدراسة على تحليل كل من القوائم والتقارير المالية التي يقدمها نظام المعلومات المحاسبي المطبق في المصرف العقاري السوري، ومدى إمكانيته على الوفاء بمتطلبات نموذجcamels والتي تعتبر من أهم الطرق المستخدمة في عملية التقويم المصرفي وعمليات الرقابة، وتوصلت الدراسة إلى أن نظام المعلومات المحاسبي المطبَق في المصرف العقاري السوري يوفر بعض المعلومات التفصيلية والتي يمكن استخدامها ,وفق نموذج camels، إلا أن هناك بعض المعلومات لا يقدمها نظام المعلومات المحاسبي ضمن التقارير والقوائم ليصار إلى استخدامها وفق هذه الطريقة . In recent years, working environment has been characterized by the tendency towards expanding the range of services and banking operations in accordance with time developments, information technology, and communications world. This side carries many positive signs that will increase customer satisfaction and confidence in the bank, which would give it a greater ability to keep its customers and attract new ones; that will be positively reflected on its performance. However, this has led the banking business to being subjected to various risks; some of these risks are associated with internal factors that belong to the bank and its management, and others are external whose source is changing the environment surrounding the banking business, and that imposes priorities on the bank to ensure survival in the banking market in light of increasing competition. The most important of these priorities is to strengthen capital and reserves consistent with risk levels imposed by this new and open environment. This study focuses on analyzing of financial lists and reports provided by the accounting information system implemented at the Real Estate Bank of Syria, and how much it can meet CAMELS requirements, being one of the most important methods used in the banking evaluation process and supervision. This research concludes that the accounting information system applied in the Real Estate Bank of Syria provides some detailed information which can be used according to the CAMELS method. However, there is some information that is not provided by the accounting information system in its reports and statements to be used according to this method.